The image of Christ in modern art - Harries, Richard, 1936- (Burlington : Ashgate Publishing Company, 2013)
The Image of Christ in Modern Art explores the challenges, presented by the radical and rapid changes of artistic style in the 20th century, to artists who wished to relate to traditional Christian imagery. In this highly illustrated book, Richard Harries looks at artists associated with the birth of modernism, such as Epstein and Rouault, as well as those with a highly distinctive understanding of religion such as Chagall and Stanley Spencer. Through a beautiful range of images and insightful text, Harries suggests that the modern movement in art has turned out to be a friend not a foe of Chr.
The break -- The explosion of modernism -- Distinctive individual visions -- Catholic elegance and joy -- The post war recovery of confidence -- Searching for new ways -- A vibrant contemporary scene.
Includes bibliographical references and index.
Print version record.
English.
Keywords: Jesus Christ -- Art; Jesus Christ; Christian art and symbolism -- Modern period, 1500-; Aesthetics, Modern -- 20th century; Aesthetics, Modern -- 21st century; ART -- Subjects & Themes -- General; Aesthetics, Modern; Christian art and symbolism -- Modern period; 1900-2099; Electronic books; Art; Electronic books